The obstacles that limit the role of civil social development committees in promoting cultural identity - Al-Dajani, Muhammad Saeed (Journal of Humanities & Social Sciences, 2022)
This study aimed at exploring the obstacles that restrict the role of the private social development committees in fostering cultural identity. It also aimed to identify the extent to which there are statistically significant differences between the responses of the participants, including some variables like gender, age, educational level, specialization, nature of work in the committee, and number of years working in the committee. To this end, this study employed the social survey method, a questionnaire, for collecting data. It was applied to the social development committees in Riyadh, targeting the entire population (the members of the boards of directors and their employees), using a comprehensive survey method. However, 89 people responded to the survey. The study concluded that the obstacles that could restrict the role of the social development committees in promoting cultural identity are the small budget of cultural programs, the lack of community members’ support for cultural activities, and the lack of suitable places to implement cultural programs. The mean was 2.27 out of 3.00, but the findings revealed that that there are no statistically significant differences between the aforementioned variables. A number of recommendations were made: providing financial support to the private social development committees to activate their role in fostering the cultural identity and taking the advantage of use of the government places to carry out their cultural programs, recruiting experts to implement programs that promote cultural identity, and establishing partnerships with cultural institutions to promote cultural identity. – This study has applied on civil social development committees in Riyadh city.